Evidence of tick-borne encephalitis virus neutralizing antibodies in Serbian individuals exposed to tick bites - Banović, Pavle; Mijatović, Dragana; Bogdan, Ivana; Simin, Verica; Meletis, Eleftherios; Kostoulas, Polychronis; Resman Rus, Katarina; Knap, Nataša; Korva, Miša; Avšič-Županc, Tatjana; Cabezas-Cruz, Alejandro (Frontiers in Microbiology, 2023)
Tick-borne encephalitis (TBE) is an emerging vector-borne and food-borne disease caused by the tickborne encephalitis virus (TBEV; Orthoflavivirus encephalitidis), with a distribution spanning the Eurasian continent. Despite its significant public health impact in various European regions, TBE remains largely underdiagnosed in Serbia due to limited awareness and diagnostic challenges. In response to this, our study aimed to comprehensively assess TBEV exposure in individuals infested with ticks and to identify potential TBEV foci within Serbia. From 2019 to 2021, we conducted an observational study involving 450 patients who reported tick infestations. Our demographic analysis revealed a median age of 38 years, with a slight male predominance among the participants. We documented tick infestations in 38 municipalities across 14 districts of Serbia, with a notable concentration in proximity to Fruška Gora Mountain. The ticks most frequently removed were Ixodes ricinus, with nymphs and adult females being the predominant stages. On average, nymphs were removed after about 27.1 hours of feeding, while adult females remained attached for approximately 44.4 hours. Notably, we found age as a significant predictor of infestation time for both nymphs and adult females. Furthermore, we detected TBEV-neutralizing antibodies in 0.66% of the serum samples, shedding light on potential TBEV foci, particularly in Fruška Gora Mountain and other regions of Serbia. In conclusion, our study emphasizes the urgent need for active TBE surveillance programs, especially in areas suspected of hosting TBEV foci, in order to assess the true TBE burden, identify atrisk populations, and implement effective preventive measures.